PREVALENSI PENYAKIT MULUT DAN KUKU (PMK) PADA SAPI DI KOTA BATU JAWA TIMUR - Wulandari, Sindi Kinasih; Anantyarta, Primadya (BIOEDUKASI (Jurnal Pendidikan Biologi), 2026)
Foot and Mouth Disease (FMD) is a highly contagious transboundary animal disease that significantly impacts the livestock sector. Batu City, one of the main cattle farming centers in East Java, has been affected by the FMD outbreak since 2022, yet local data on its prevalence and associated risk factors remain limited. This study aims to determine the prevalence of FMD in cattle in Batu City, identify key transmission risk factors, and evaluate the roles of both the government and farmers in controlling the outbreak. A descriptive quantitative method was employed using a cross-sectional approach, field interviews, and literature review. The data showed a total cattle population of 15,413, with 139 sick, 106 dead, 3,805 recovered, and 20 culled. The prevalence of FMD based on affected populations was 3.21%, and 0.90% based on the total cattle population. Major risk factors included communal housing systems, high animal mobility, inadequate biosecurity practices, uneven vaccination coverage, and low farmer awareness. The Batu City Government responded through mass vaccination, farmer education, livestock traffic control, and financial compensation for affected farmers. These findings highlight the importance of locally tailored disease control strategies to prevent further spread of FMD. The results are expected to support the development of effective and evidence-based policy interventions at the regional level.